2022
DOI: 10.3390/molecules27020358
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan and Alginate from the Brown Algae Colpomenia sinuosa and Their Combination with Vitamin C Trigger Apoptosis in Colon Cancer

Abstract: Brown seaweeds are producers of bioactive molecules which are known to inhibit oncogenic growth. Here, we investigated the antioxidant, cytotoxic, and apoptotic effects of two polysaccharides from the brown algae Colpomenia sinuosa, namely fucoidan and alginate, in a panel of cancer cell lines and evaluated their effects when combined with vitamin C. Fucoidan and alginate were isolated from brown algae and characterized by HPLC, FTIR, and NMR spectroscopy. The results indicated that highly sulfated fucoidans h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 81 publications
0
15
0
1
Order By: Relevance
“…For instance, the phenolic content, i.e., phlorotannins and flavonoids, in F. vesiculosus that has been recently determined by Obluchinskaya et al was at 72.4–158.1 mg phloroglucinol equivalent/g dried weight (DW) algae based on geographic locations of algae harvesting [ 52 ]. Moreover, the phenolic and protein contents in other species of brown seaweeds as Colpomenia sinuosa were at 0.045 mg GAE/g DW and 1.88%, respectively [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the phenolic content, i.e., phlorotannins and flavonoids, in F. vesiculosus that has been recently determined by Obluchinskaya et al was at 72.4–158.1 mg phloroglucinol equivalent/g dried weight (DW) algae based on geographic locations of algae harvesting [ 52 ]. Moreover, the phenolic and protein contents in other species of brown seaweeds as Colpomenia sinuosa were at 0.045 mg GAE/g DW and 1.88%, respectively [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, in the HCT-116 cell line, the TPs and APs showed 50% inhibitory concentration (IC 50 ) values of 760 µg mL −1 and 1370 µg mL −1 , respectively ( Figure 6 A). Recently, sulfated polysaccharides from the brown algae Colpomenia sinuosa (unknown Mw, sulfate content 18.8%, molar % 67.4, 5.94, 3.58, 2.62, 5.45, and 3.4 for fucose, galactose, mannose, xylose, glucosa, and arabinose, respectively), at a concentration of 750 µg mL −1 , showed a cell inhibition ability of 45% on HCT-116 cell line [ 67 ]. Conversely, sulfated polysaccharides (ScF2) extracted from the brown seaweed Saccharina cichorioides are not toxic against HCT-116 cells at doses up to 800 µg mL −1 [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biobased fibers have good antibacterial, biodegradable and biocompatible properties in vivo and in vitro (Xu et al, 2022), so the application of biobased fibers in biomedical functions has a good prospect. Alginate extracted from kelp or sargassum algae of brown algae is a group of natural polysaccharides with linear anions (Gheorghita Puscaselu et al, 2020;Al Monla et al, 2022). Alginate fiber is non-toxic, with rich sources, high hygroscopicity, good biodegradability, and biocompatibility, and can be used as an excellent medical textile fiber (Aderibigbe and Buyana, 2018).…”
Section: Biomedical Functionsmentioning
confidence: 99%